The stricter criteria for Class I CRT indication suggested by the 2016 ESC Guidelines reliably exclude patients with a worse prognosis in comparison with the 2013 ESC indication criteria. (15th December 2018) - Bertaglia, Emanuele; Reggiani, Albino; Palmisano, Pietro; D'Onofrio, Antonio; De Simone, Antonio; Caico, Salvatore I.; Pecora, Domenico; Arena, Giuseppe; Marini, Massimiliano; Ricciardi, Giuseppe; Badolati, Sandra; Spotti, Alfredo; et al.
Abstract: Background: The European Society of Cardiology (ESC) Guidelines published in 2016 modified indications for cardiac resynchronization therapy (CRT) in comparison with the 2013 ESC Guidelines. The aim of this analysis was to evaluate the impact of the stricter criteria suggested by the 2016 ESC Guidelines on patient outcome in a real-world population. Methods: We collected data on 930 consecutive patients with complete outcome information who had undergone CRT implantation from 2011 to 2013 from the CRT-MORE registry. Patients were classified according to 2013 (Reference) and 2016 (Current) ESC Guidelines. The primary end-point of the study was death from any cause and heart failure hospitalization. Results: According to the Reference Guidelines, 650 (69.9%) patients met Class I indications, 190 (20.4%) Class IIa, 39 (4.2%) Class IIb and 51 (5.5%) Class III. According to the Current Guidelines, 563 (60.5%) patients met Class I indications, 145 (15.6%) Class IIa, 108 (11.6%) Class IIb and 114 (12.3%) Class III. On comparing the Reference and Current Guidelines, the 538 patients who confirmed their Class I indication had a better outcome in terms of freedom from the combined end-point of heart failure (HF) hospitalization or death from any cause (hazard ratio (HR) of 0.64; 95% CI 0.42 to 0.99; p = 0.0436) when compared to the 112 patients who lost their class I indication (84 moved to class IIb and 28 moved to class III). Conclusions: The stricter criteria for Class I CRT indication suggested by the 2016 ESC Guidelines excluded about 20% of patients with a worse prognosis. Clinical Trial Registration: CRT MORE: Cardiac Resynchronization Therapy Modular Registry URL:http://clinicaltrials.gov/Identifier:NCT01573091 . Highlights: In a real-world population, application of the new stricter criteria for Class I CRT indication suggested by the 2016 ESC Guidelines identified a population with better outcome in comparison with the 2013 ESC Guidelines Patients who maintained Class I indication improved their clinical response in comparison with those downgraded on the basis of Current Guidelines As clinical guidelines are usually based on the results of large clinical trials, analyzing the effects of applying new clinical guidelines in the real world seems important in order to validate the choices of the task forces